Features and prospects of implementation of the integrated Lean Six Sigma methodology at the enterprise - N. N. Trofimova (Вестник университета)
The article considers the integrated Lean Six Sigma methodology. The author shows that today enterprises use the Lean Six Sigma methodology to improve production indicators, optimize the product portfolio, achieve strategic goals. The paper clarifies the essence of the American (Six Sigma) and Japanese (Lean) enterprise management methodology. The study highlights some features, system tools and methods of continuous improvement in the framework of the implementation of the integrated Lean Six Sigma methodology at the enterprise. The article highlights a number of key success factors for the implementation of this methodology. The paper proposes the criteria for assessing the readiness of the enterprise to its implementation. The scientific novelty of the study is that the author identified the advantages and problems of implementing the Lean Six Sigma methodology at enterprises. The author made a proposal on the need for mandatory assessment of the company's readiness to work on the Lean Six Sigma methodology using fuzzy logic tools, and also highlighted the stages of its implementation. The practical significance of the work done is that it can serve as a basis for further scientific research in the field of the Lean Six Sigma methodology.